2022
DOI: 10.3390/cells11223635
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Contribution to Inflammation in Diabetic Kidney Disease

Abstract: Diabetes is the leading cause of chronic kidney disease worldwide. Despite the burden, the factors contributing to the development and progression of diabetic kidney disease (DKD) remain to be fully elucidated. In recent years, increasing evidence suggests that mitochondrial dysfunction is a pathological mediator in DKD as the kidney is a highly metabolic organ rich in mitochondria. Furthermore, low grade chronic inflammation also contributes to the progression of DKD, and several inflammatory biomarkers have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 155 publications
0
5
0
Order By: Relevance
“…With this CONUT score, this study found that compared with normal nutritional status, moderate and severe malnutrition (a score of 2–12) was associated with an increased risk of all-cause mortality. As a dimension of nutritional status assessment, inflammation facilitates the development of DKD,24 possibly through releasing interleukin-1 (IL-1) from monocytes, which might initiate major complications and elevated mortality 25. Additionally, inflammation is correlated with malnutrition and protein-energy wasting, potentially contributing to mortality in DKD 26.…”
Section: Discussionmentioning
confidence: 99%
“…With this CONUT score, this study found that compared with normal nutritional status, moderate and severe malnutrition (a score of 2–12) was associated with an increased risk of all-cause mortality. As a dimension of nutritional status assessment, inflammation facilitates the development of DKD,24 possibly through releasing interleukin-1 (IL-1) from monocytes, which might initiate major complications and elevated mortality 25. Additionally, inflammation is correlated with malnutrition and protein-energy wasting, potentially contributing to mortality in DKD 26.…”
Section: Discussionmentioning
confidence: 99%
“…In the Chronic Renal Insu ciency Cohort (CRIC) study 26 , surrogate marker of in ammation (such as CRP, TNF-α, IL-1β, IL-1 receptor antagonists, and IL-6) were positively associated with proteinuria and negatively associated with renal function. Recently, chronic in ammation has also been shown to contribute to the aggravation of diabetic kidney disease, and several in ammatory biomarkers have been considered as prognostic markers to risk-stratify patients for disease progression and all-cause mortality 27 . However, whether remnant cholesterol contributes to DN progression through the mechanism of insulin resistance and low-grade system in ammation remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Queuine is a pyrrolopyrimidine-containing analog of guanine ( Figure 1 ) that is exclusively synthesized by bacteria and found in most eukaryotes, including humans who acquire queuine from their own gut microbiota and a diet that contains this bacterial-derived molecule ( Fergus et al, 2015 ; Richard et al, 2021 ). DKD progression is associated with low-grade inflammation and mitochondrial dysfunction ( Zhan et al, 2015 ; Ducasa et al, 2019 ; Na et al, 2021 ; Mitrofanova et al, 2022 ). Queuine is reported to be involved in the recovery of mitochondrial dysfunction and has a protection effect in neurodegeneration diseases ( Zheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%